2008
DOI: 10.1177/1098300708322444
|View full text |Cite
|
Sign up to set email alerts
|

Effective Behavior and Instructional Support

Abstract: The purpose of this article is to describe the development and 10-year implementation of the effective behavior and instructional support model in a midsized northwestern Oregon school district. The district experienced a sustained reduction in students' discipline referral rates, an increase in the percentage of students on track for early reading benchmarks, and an improvement in special education evaluation of learning disabilities. These important outcomes were associated with the systematic integration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Numerous studies have evaluated the effects of SWPBIS on student behavioral outcomes and found that, when SWPBIS is implemented with fidelity, improvements are apparent in office discipline referrals (ODRs), disciplinary actions, school climate and safety, academic achievement, bullying and peer victimization, and organizational health (Bradshaw, Koth, Bevans, Ialongo, & Leaf, 2008; Bradshaw, Koth, Thornton, & Leaf, 2009; Bradshaw, Mitchell, & Leaf, 2010; Childs, Kincaid, George, & Gage, 2016; Gage, Leite, Childs, & Kincaid, 2017; Horner, Sugai, & Anderson, 2010; Sadler & Sugai, 2009; Simonsen et al, 2012; Waasdorp, Bradshaw, & Leaf, 2012). Despite a large body of research, few SWPBIS studies have used experimental or quasi-experimental designs (QEDs) to compare disciplinary actions among schools implementing SWPBIS to schools that are not.…”
Section: Empirical Support For Swpbismentioning
confidence: 99%
“…Numerous studies have evaluated the effects of SWPBIS on student behavioral outcomes and found that, when SWPBIS is implemented with fidelity, improvements are apparent in office discipline referrals (ODRs), disciplinary actions, school climate and safety, academic achievement, bullying and peer victimization, and organizational health (Bradshaw, Koth, Bevans, Ialongo, & Leaf, 2008; Bradshaw, Koth, Thornton, & Leaf, 2009; Bradshaw, Mitchell, & Leaf, 2010; Childs, Kincaid, George, & Gage, 2016; Gage, Leite, Childs, & Kincaid, 2017; Horner, Sugai, & Anderson, 2010; Sadler & Sugai, 2009; Simonsen et al, 2012; Waasdorp, Bradshaw, & Leaf, 2012). Despite a large body of research, few SWPBIS studies have used experimental or quasi-experimental designs (QEDs) to compare disciplinary actions among schools implementing SWPBIS to schools that are not.…”
Section: Empirical Support For Swpbismentioning
confidence: 99%
“…The SWPBIS and SWRM share many components including a tiered model of prevention, which identifies struggling students through systematic screening and provides increasing levels of support meant to match the needs of students (McIntosh, Horner, Chard, Boland, & Good, 2006;Sadler & Sugai, 2009). The aim of PBIS, and its universal, school-wide component SWPBIS, is to improve student adjustment, social behavior, and academic success through methods that increase positive behavior and make problem behaviors irrelevant, inefficient, or ineffective (Bambara & Kern, 2005;Carr et al, 2002).…”
Section: Ebissmentioning
confidence: 99%
“…PBIS relies on a systems approach that incorporates theoretically supported principles from applied behavior analysis and EBPs, such as explicit instruction and data-based decision-making (Horner et al, 2005). When SWPBIS successfully reduces problem behavior, it helps school specialists identify students who may have emotional or behavioral disorders by reducing the false-positives-those students who appear to have challenging behaviors but quickly respond to universal supports-and providing data to support special education decisions (Horner et al, 2005;Sadler & Sugai, 2009).…”
Section: Ebissmentioning
confidence: 99%
“…Both systems use a multitiered model of prevention that identifies struggling students through systematic screening and provides increasing levels of support that match the needs of students (McIntosh, Horner, Chard, Boland, & Good, 2006; Sadler & Sugai, 2009). Both systems encourage teachers, school administrators, and district leaders to collaborate and make decisions based on student performance data (Ervin, Schaughency, Goodman, McGlinchey, & Matthews, 2006; Sadler & Sugai, 2009). A review by Stewart, Brenner, Martella, and Marchand‐Martella (2007) indicates that an integrated, three‐tiered model may lead to larger literacy gains than a reading intervention alone.…”
Section: Effective Behavioral and Instructional Support Systemsmentioning
confidence: 99%
“…Demonstrations of combining SWPBIS and the SWRM have been addressed in the literature from district and state perspectives. From a district perspective, Sadler and Sugai (2009) report that collaboration and data‐based teams were at the core of the district's blended model. The district reported an increase over time in levels of implementation of SWPBIS on the School‐Wide Evaluation Tool (SET; Todd et al, 2005), an increase in the percentage of students reaching grade‐level goals, and a decrease in the amount of office discipline referrals.…”
Section: Blending School‐wide Behavior and Literacy Systemsmentioning
confidence: 99%